Geomicrobiology and Biogeochemistry of Precious Metals - Frank Reith (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Precious metals continue to have economic and sociocultural importance, as their usage evolves and diversifies over time. Today, the industrial application of precious metals is increasing with the development of scientific and technological innovations. Especially, the biological cycling of these metals is receiving more and more attention, as the microbiota may be key to a range of issues regarding exploration, ore-processing and metallurgy, and the processing of electron waste. In this volume, we focus on enhancing the fundamental understanding of the biological processes that drive noble metal cycling and examine how this knowledge may be turned into biotechnolical applications.